Hubungan Manajemen Waktu Perawat dengan Pendokumentasian Pemberian Asuhan Keperawatan di Ruang Rawat Inap di RS Islam Banjarmasin - Ahmad Julkifli; Rida' Millati; Yustan Azidin; Herman Ariadi (Malahayati Nursing Journal, 2026)
ABSTRACT Time management affects the service and quality of nursing care documentation, which can pose medical and legal risks for patients and institutions. This research aims to determine the relationship between nurses' time management and the documentation of nursing care provided in the Inpatient Ward of Banjarmasin Islamic Hospital. This research uses a quantitative analytical correlational design with a cross-sectional approach. The population consists of all registered nurses and team leaders in the inpatient wards of the Islamic Hospital in Banjarmasin, totaling 66 individuals. A sample of 57 respondents was selected using total sampling technique. Time management was measured using a questionnaire that had been tested for validity (r 0.361) and reliability (Cronbach's alpha 0.70). The results of the data analysis show that the majority of respondents have good time management (46 respondents, 80.7%), while the majority of nursing care documentation is in the good category (56 respondents, 98.2%). The bivariate test using Spearman Rho analysis with a significance level of 0.05 showed a significant relationship between nurses' time management and nursing care documentation in the Inpatient Ward of the Islamic Hospital in Banjarmasin, with an r value of 0.273 and p = 0.040 (p 0.05). There is a significant positive relationship between nurses' time management and the documentation of nursing care provision in the Inpatient Ward of the Islamic Hospital in Banjarmasin. Nursing managers are expected to enhance time management training to optimize documentation and the quality of nursing care. Keywords: Time Management, Nursing Care Documentation, Inpatient Ward Nurses.  ABSTRAK Manajemen waktu berpengaruh terhadap pelayanan dan kualitas pendokumentasian asuhan keperawatan, yang dapat menimbulkan risiko medis dan hukum bagi pasien serta institusi. Penelitian ini untuk mengetahui hubungan manajemen waktu perawat dengan pendokumentasian pemberian asuhan keperawatan di Ruang Rawat Inap RS Islam Banjarmasin. Penelitian ini menggunakan desain kuantitatif analitik korelasional dengan pendekatan cross sectional. Populasi adalah seluruh perawat pelaksana dan ketua tim di ruang rawat inap RS Islam Banjarmasin sebanyak 66 orang, dengan sampel 57 responden yang diambil menggunakan teknik total sampling. Manajemen waktu diukur menggunakan kuesioner yang telah diuji validitas (r 0,361) dan reliabilitas (Cronbach's alpha 0,70). Hasil dari analisis data sebagian besar responden memiliki manajemen waktu kategori baik (46 responden, 80,7%), sementara pendokumentasian asuhan keperawatan mayoritas berada pada kategori baik (56 responden, 98,2%). Uji bivariat menggunakan analisis Spearman Rho dengan tingkat signifikansi p = 0,040 (p 0,05) menunjukkan terdapat hubungan signifikan antara manajemen waktu perawat dengan pendokumentasian asuhan keperawatan di Ruang Rawat Inap RS Islam Banjarmasin dengan nilai r = 0,273 dan. Terdapat hubungan positif signifikan antara manajemen waktu perawat dengan pendokumentasian pemberian asuhan keperawatan di Ruang Rawat Inap RS Islam Banjarmasin. Manajer keperawatan diharapkan meningkatkan pelatihan manajemen waktu untuk mengoptimalkan pendokumentasian dan mutu asuhan keperawatan. Kata Kunci: Manajemen Waktu, Pendokumentasian Asuhan Keperawatan, Perawat Ruang Rawat Inap.